2000
DOI: 10.1023/a:1006404621724
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Wild-type plastocyanin from the cyanobacterium Synechocystis sp. PCC 6803 does not form any kinetically detectable transient complex with Photosystem I (PS I) during electron transfer, but the D44R/D47R double mutant of copper protein does [De la Cerda et al. (1997) Biochemistry 36: 10125-10130]. To identify the PS I component that is involved in the complex formation with the D44R/D47R plastocyanin, the kinetic efficiency of several PS I mutants, including a PsaF-PsaJ-less PS I and deletion mutants in the lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
19
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 15 publications
6
19
0
Order By: Relevance
“…3, left). These maxima are characteristic for cytochrome c 550 (27,28); the apparent low redox potential is in agreement with the Ϫ250 mV level reported for cytochrome c 550 for other cyanobacteria (28,29). An ascorbate-reduced minus ferricyanide-oxidized difference spectrum showed merely the characteristic peak of cytochrome b 559 at approximately 559 nm (Fig.…”
Section: Isolation and Biochemical Characterization Of A Dimeric Pssupporting
confidence: 89%
“…3, left). These maxima are characteristic for cytochrome c 550 (27,28); the apparent low redox potential is in agreement with the Ϫ250 mV level reported for cytochrome c 550 for other cyanobacteria (28,29). An ascorbate-reduced minus ferricyanide-oxidized difference spectrum showed merely the characteristic peak of cytochrome b 559 at approximately 559 nm (Fig.…”
Section: Isolation and Biochemical Characterization Of A Dimeric Pssupporting
confidence: 89%
“…The recent resolution of the threedimensional structure of the soluble form of cyt c 550 from three cyanobacteria, Synechocystis sp. PCC 6803 (9), Arthrospira maxima (10), and Thermosynechococcus elongatus (11) has confirmed a previously proposed bis-histidine coordinated heme that is very unusual for monoheme c-type cytochromes (8,11,12). Crystal structures of both isolated and PSII-bound forms of cyt c 550 show that the protein presents a hydrophobic inner core typical of monoheme cytochromes c, with three helices forming a nest for the prosthetic group and a fourth helical segment in the N-terminal domain protecting the heme from solvent, indicating that the heme structure is not very different from most c-type cytochromes (13).…”
supporting
confidence: 82%
“…Cyt c 550 , encoded by the psbV gene, is a monoheme protein with a molecular mass of Ϸ 15 kDa and an isoelectric point between 3.8 and 5.0 (7,8). The recent resolution of the threedimensional structure of the soluble form of cyt c 550 from three cyanobacteria, Synechocystis sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The low midpoint redox potential (EЈ m ) values of the purified cyt c 550 (from Ϫ250 to Ϫ314 mV (1,12,13)) seems incompatible with a redox function in PS II electron transfer. However, we have recently demonstrated that the cyt c 550 from the thermophilic cyanobacteria Thermosynechococcus elongatus has a significantly higher EЈ m value when it is bound to the PS II (Ϫ80/Ϫ100 mV) compared with its soluble form after its extraction from PS II (Ϫ240 mV at pH 6) (14).…”
mentioning
confidence: 99%